1998
DOI: 10.1002/(sici)1099-1581(199802)9:2<134::aid-pat725>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sizing materials of carbon fiber on solid-state cure of poly(p-phenylene sulfide)

Abstract: The effect of sized carbon fibers on the solid‐state cure of poly(p‐phenylene sulfide) (PPS) was studied using differential scanning calorimetry. PPS resin reinforced with sized carbon fiber exhibited the largest cure peak for all cure temperatures and showed a second peak at low cure temperature which was absent in both PPS reinforced with desized carbon fiber and neat PPS resin. In a separate experiment in which epoxy prepolymer/PPS mixture was cured, the exothermic reaction was related to the presence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In Figure 2a, it is noticed that the characteristic peaks include O 1s (532 eV), C 1s (284 eV), and S 2p (163 eV) of PPS, and the peak value of O 1s increases significantly. Table 1 summarizes 27 It is also observed that there are oxygen atoms in the untreated samples, and the reason could be that oxidation reaction of PPS might already occur in the melt mixing and/or hot pressing process (∼290 °C). In thermal oxidation, a strong light absorbing group similar to quinone would frequently form, 28 and it is also confirmed from Figure 2f that the color of the sample becomes darker after thermal oxidation compared with the untreated sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 2a, it is noticed that the characteristic peaks include O 1s (532 eV), C 1s (284 eV), and S 2p (163 eV) of PPS, and the peak value of O 1s increases significantly. Table 1 summarizes 27 It is also observed that there are oxygen atoms in the untreated samples, and the reason could be that oxidation reaction of PPS might already occur in the melt mixing and/or hot pressing process (∼290 °C). In thermal oxidation, a strong light absorbing group similar to quinone would frequently form, 28 and it is also confirmed from Figure 2f that the color of the sample becomes darker after thermal oxidation compared with the untreated sample.…”
Section: Resultsmentioning
confidence: 99%
“…After being treated at 250 °C for 12 h, the proportion of −SO–, −SO 2 –, and −C–O–C– increased, indicating that cross-linking and further oxidation occur under this treatment condition. At the early beginning of cross-linking, it tends to form more stable −SO–than −S–; when oxidation is prolonged, it tends to generate even more stable −SO 2 – than −SO– . It is also observed that there are oxygen atoms in the untreated samples, and the reason could be that oxidation reaction of PPS might already occur in the melt mixing and/or hot pressing process (∼290 °C).…”
Section: Resultsmentioning
confidence: 99%